A moodle course to substitute resuscitation teaching in a medical curriculum during the COVID-19 pandemic: A prospective pilot study - Ettl, Florian; Schriefl, Christoph; Grafeneder, Jürgen; Thallner, Dominik Gabriel; Mueller, Matthias; Fischer, Eva; Schlegel, Raphael; Sigmund, Thorsten; Holzer, Michael; Schnaubelt, Sebastian (Frontiers in Public Health, 2022)
Background: Face-to-face medical education was restricted during the COVID-19 pandemic, leading to alternative teaching methods. Moodle® - an online course format - has not yet been sufficiently evaluated for its feasibility and effectiveness in teaching cardiopulmonary resuscitation. Methods: Medical students in the 8th semester took part in a Moodle® course teaching basic life support, the ABCDE-approach, airway management and advanced life support. The content was presented using digital background information and interactive videos. A multiple-choice test was conducted at the beginning and at the end of the course. Subjective ratings were included as well. Results: Out of 594 students, who were enrolled in the online course, 531 could be included in this study. The median percentage of correctly answered multiple-choice test questions increased after completing the course (78.9%, IQR 69.3 - 86.8 vs. 97.4%, IQR 92.1 – 100, p<0.001). There was no gender difference in the median percentage of correctly answered questions before (female: 79.8%, IQR 70.2 - 86.8, male: 78.1%, IQR 68.4 - 86.8, p=0.412) or after (female: 97.4%, IQR 92.1-100, male: 96.5%, IQR 92.6 - 100, p=0.233) the course. On a 5-point Likert-scale, 78.7% of students self-reported ≥ 4 when asked for a subjective increase in knowledge. Noteworthy, on a 10-point Likert-scale, male students self-reported a higher confidence in performing CPR (female 6 (5-7), male 7 (6-8), p < 0.001). Conclusion: The Moodle® course led to a significant increase in theoretical knowledge. It proved to be a feasible substitute for face-to-face courses - both objectively and subjectively.